Jejuno-jejunal intussusception – A cadaveric case report - Ms MONICA GOPALAKRISHNAN; Dr P K SANKARAN; Dr GUNAPRIYA RAGHUNATH; Mr SACHIN SAGAR; Mr ADAPA VENKATA KRISHNA REDDY; Ms BINDHU CHARLES S. (International Journal of Pharma and Bio Sciences, 2017)
During routine cadaveric dissection a rare condition jejunojejunal intussusception was found in an adult cadaver. It accounts for 5-10% of all intussuception and 1% of all bowel obstructions.The part of the intestine beyond the intussuception may or may not show necrosis and obstruction. Ultrasound and CT scans are the two most important radiological methods to diagnose intussusception.